Policy on Criminal Law Enforcement Against Illegular Drugs Syndicate Performers What Members of the Police of the Republic of Indonesia Done - Zainab Ompu Jainah (International Journal of Science and Society, 2022)
Every member of the National Police should ideally be a law enforcement officer who carries out maintaining public security and order, enforcing the law, and providing protection, shelter, and service to the community. In fact, there are members of the National Police who are part of a syndicate of narcotics traffickers. Therefore, the criminal law enforcement policies are implemented against the perpetrators. The problem of this research is how the policy of criminal law enforcement against drug dealer syndicates is carried out by members of the National Police and what are the legal consequences for the perpetrators of illicit drug trafficking syndicates carried out by members of the Indonesian National Police. This study uses a normative juridical approach based on secondary data which was analyzed qualitatively. The results of this study indicate that the policy of law enforcement against the perpetrators of drug trafficking syndicates carried out by members of the National Police through the means of criminal law is the settlement of cases using general criminal procedure law through the general court. The legal instrument used is Law Number 35 of 2009 concerning Narcotics. In addition, law enforcement against perpetrators of drug trafficking syndicates carried out by members of the National Police is also carried out using the enforcement of the Police Code of Ethics through the Police Code of Ethics trial. The legal consequences for perpetrators of illicit drug trafficking syndicates carried out by members of the Indonesian National Police are that the perpetrators will be faced with two legal instruments at once, namely general criminal justice in accordance with the provisions of the criminal procedure law and can be sentenced to criminal penalties in accordance with the article of the Narcotics Law that is violated and enforcement the law through an ethics trial by the internal police, with the most severe sanctions against the perpetrators being subject to ethical sanctions in the form of dishonorable dismissal as members of the police.